The Influence of Product Quality on Customer Loyalty at Groei Coffee Bandung in 2026 - Muhammad Raffy Asri; Leni Cahyani (Eduvest - Journal of Universal Studies, 2026)
This study aims to analyze the influence of product quality on customer loyalty at Groei Coffee Bandung in 2026. The background of this research is the increasing competition in the coffee shop industry, which requires businesses to maintain product quality to sustain customer loyalty. This study uses a quantitative approach with a survey method involving 100 respondents who are active customers of Groei Coffee. Data were collected through questionnaires using a 5-point Likert scale and analyzed using descriptive statistics and simple linear regression with the assistance of SPSS software. The results show that product quality has a positive and significant effect on customer loyalty, with a regression equation of Y = 13.289 + 0.250X and a significance value of 0.000 < 0.05. Descriptive analysis indicates that product quality is rated in the “satisfied” category with an average score of 79.02%, while customer loyalty also falls into the “satisfied” category with an average score of 79.04%. The coefficient of determination (R² = 0.234) shows that product quality explains 23.4% of customer loyalty, while the remaining 76.6% is influenced by other factors. These findings suggest that maintaining product quality, particularly in terms of taste consistency, reliability, and presentation aesthetics, plays an important role in enhancing customer loyalty.